PEMBELAJARAN ADVOKASI: Solusi Alternatif Meningkatkan Hasil Belajar Siswa di Abad 21 - 'Aabidah Ummu 'Aziizah; Nisa Bella; Ibrahim Ibrahim (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
This study aims to determine the extent of the development of the implementation of advocacy learning and develop it as an alternative solution in improving student learning outcomes in the 21st century. This research method uses qualitative research with a library research approach and is descriptive in nature and applies the Systematic Literature Review (SLR) method. Data collection is done by looking at previous research empirically whether it is qualitative, quantitative or mixed methods. Meanwhile, the analysis and evaluation of the data was carried out using a data table containing the classification of previous researches focused on each discussion of the keywords in this study. The results of this study indicate that (1) research on advocacy learning models still revolves around a micro scope which is limited in its application to debate activities and subject matters that are open-ended and only focused on the student's point of view (2) The development of advocacy learning models can be done through macro actualization of advocacy models on various learning methods and not only limited to exact or non-exact topics, open-ended or closed-ended and advocacy model reviews can be intended for two points of view, namely teachers and students.